Section 1983 litigation: An effective remedy to police misconduct or an insidious federalism? - Barrineau, Harry E. (American journal of criminal justice, 1984)
In recent years the federal courts have experienced a dramatic increase in civil suits alleging police misconduct under the federal provision, 42 U.S.C. Section 1983, which was originally enactd as part of the Civil Rights Act of 1871. Section 1983, presently the second most litigated provision of the United States Code, grants a private right of action for redressing violations of federal and Constitutional rights committed by persons (including municipalities) acting under color of state law. The recent development of Section 1983 as a mechanism for controlling police misconduct has profound implications for New Federalism, public official conduct and traditional legal doctrines (such as the exclusionary rule). This study reviews the legal basis for civil liability remedies, examines the impact of recent developments on police behavior, and explores the policy considerations underlying an assessment of this expanding legal remedy as a viable option in preventing police misconduct.